4-Axis CNC Machine Tool for Relief Grinding Sphere Gear Hob - Hu Zhanqi; Li Yukun (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
A new 4-axis machine tool, which is used for relief grind of sphere gears hob including spherical hob, elliptic hob and arc surface hob, is developed. The principle of relief machining of spherical hob is introduced first. Transmitting system, numerical system and some key techniques are then introduced. The machine tool can be reconfigured in machining of arc worms and spatial cams beside of machining of spherical hob. Four forms of the machine tool for machining different workpiece are also introduced. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1557